1990
DOI: 10.1046/j.1537-2995.1990.30590296383.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of anti‐HCV among Chinese voluntary blood donors in Taiwan

Abstract: In Taiwan, the prevalence of circulating anti-HCV is 2 percent among first-time voluntary Chinese blood donors, 10 percent among donors with elevated ALT levels (greater than 45 IU/L), and higher among older men. The carrier rate for HBsAg was 18.6 percent and the frequency of positive HBV marker(s) (HBsAg, anti-HBc, anti-HBs) was 86.4 percent among first-time donors. There is no significant correlation between HBV and HCV infections in Taiwan, because there is no significant difference in the frequency of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…This finding is markedly different from those in other studies which reported a much lower frequency (0.5 to 1.%) in industrialized countries also consisting entirely of voluntary blood donors [2]. Even in blood donors with elevated alanine transaminase (ALT) levels, the prevalence of anti-HCV was only 5% in Italy [3J and 10% in Taiwan [4]. All seropositive Egyptians in this study had ALT levels within the reference range (2-50 IU/L).…”
mentioning
confidence: 66%
“…This finding is markedly different from those in other studies which reported a much lower frequency (0.5 to 1.%) in industrialized countries also consisting entirely of voluntary blood donors [2]. Even in blood donors with elevated alanine transaminase (ALT) levels, the prevalence of anti-HCV was only 5% in Italy [3J and 10% in Taiwan [4]. All seropositive Egyptians in this study had ALT levels within the reference range (2-50 IU/L).…”
mentioning
confidence: 66%
“…Surveys from North America [11] indicate that the prevalence may vary widely (0.4 to 1.0%), depending on the geographical area. In contrast, a provisional study of 500 first-time donors conducted in Taiwan [12] indicated a 2% prevalence of anti-HCV.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, ALT had been used as a surrogate marker for non-A, non-B hepatitis in the general population [11]. This practice had recently been con firmed by anti-HCV tests [9,26]. Furthermore, a recent study showed that in anti-HCV-positive HD patients with biopsy-proven liver diseases, only 21.2% had persistently normal serum transaminase levels [24], Thus, abnormal serum transaminase levels are clearly associated with liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, the prevalence of hepatitis B surface antigen (HBsAg) positivity is as high as 15-20% [8], while the prevalence of anti-hepatitis C virus antibody (anti-HCV) is only 1-2% [8,9], In the HD popu lation, the HBsAg prevalence is likewise 15-20%, al though the anti-HCV prevalence is as high as 44.6-47.2% [2, 3], Accepted: July 13.1994…”
Section: Introductionmentioning
confidence: 99%